The Development Of Speaking Skills In Children Aged 5–6 Years Through Islamic Values-Based Hand Puppet Media At Ra Mambaul Ulum Sukanagara - Suci Nurul Pazri; Eva Manfaatin Kartadinata; Ika Rustika Zainah (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Speaking skills are essential for young children because they support communication, confidence, social interaction, and learning readiness. However, several children in Group B at Raudhatul Athfal Mambaul Ulum Sukanagara still showed limited confidence in answering questions, expressing opinions, asking simple questions, and retelling stories. **This condition reduced children's participation in classroom interactions and limited opportunities for active language development. Although hand puppet media have been widely used to support speaking skills, studies integrating Islamic values into hand puppet-based learning remain limited.** This study aimed to improve the speaking skills of children aged five to six years through **Islamic values-based hand puppet media. The study employed Classroom Action Research using descriptive quantitative and qualitative approaches. The participants were 15 Group B children. Data were collected through observation, interviews, documentation, and field notes. The intervention was conducted in two cycles consisting of planning, action, observation, and reflection. The findings showed a continuous improvement in children's speaking skills. The average achievement increased from 48.0% in the pre-cycle stage to 60.0% in Cycle I and reached 86.6% in Cycle II. **Children became more active in answering questions, identifying characters and objects in stories, expressing opinions and feelings, asking simple questions, and retelling story content with greater confidence.** In addition, the stories and dialogues presented through the hand puppets introduced values such as honesty, politeness, responsibility, helpfulness, and respect for others. The study concludes that Islamic values-based hand puppet media provide an enjoyable and meaningful learning experience that effectively improves children's speaking skills while simultaneously supporting the development of positive character values.